An analysis of the presence of egyptian and mesopotamian artifacts in elementary school mathematics textbooks - Trindade, Thereza Cristinna Vieira (2024)
This research aimed to research the way in which the History of Mathematics is presented regarding Mesopotamian and Egyptian artifacts in the textbooks of The Achievement of Mathematics collection of the final years of elementary school used by the public education network in the City of São Luís-MA. Methodologically, a documentary research with a qualitative approach was developed to analyze the books in the collection approved by PNLD 2018. The results found throughout the analysis process indicated that the authors represented the historical context of Mathematics succinctly. Regarding the use of images of Mesopotamian and Egyptian artifacts, it was possible to observe that they are placed in a merely demonstrative way without any information or demonstration of the existing mathematical knowledge that will arouse the student's interest in understanding these artifacts, considering the mathematical forms in which ancient civilizations used it and the needs in which Mathematics was created as a way to meet the needs of certain people.